Intensive five-drug antiretroviral therapy regimen versus standard triple-drug therapy during primary HIV-1 infection (OPTIPRIM-ANRS 147): a randomised, open-label, phase 3 trial. Issue 4 (April 2015) - Chéret, Antoine; Nembot, Georges; Mélard, Adeline; Lascoux, Caroline; Slama, Laurence; Miailhes, Patrick; Yeni, Patrick; Abel, Sylvie; Avettand-Fenoel, Véronique; Venet, Alain; Chaix, Marie-Laure; Molina, Jean-Michel; et al.
Summary Background Early combination antiretroviral therapy (cART) initiation at the time of primary HIV-1 infection could restrict the establishment of HIV reservoirs. We aimed to assess the effect of a cART regimen intensified with raltegravir and maraviroc, compared with standard triple-drug cART, on HIV-DNA load. Methods In this randomised, open-label, phase 3 trial, we recruited patients from hospitals across France. Inclusion criteria were primary HIV-1 infection (an incomplete HIV-1 western blot and detectable plasma HIV-RNA), with either symptoms or a CD4+ cell count below 500 cells per μL. Patients were randomly assigned (1:1) to an intensive, five-drug cART regimen (raltegravir 400 mg and maraviroc 150 mg twice daily, and a fixed-dose combination of tenofovir disoproxil fumarate 300 g plus emtricitabine 200 g, darunavir 800 g, and ritonavir 100 g once daily) or a standard triple-drug cART regimen (tenofovir disoproxil fumarate 300 g plus emtricitabine 200 g, darunavir 800 g, and ritonavir 100 g once daily) using a predefined randomised list generated by randomly selected variable block sizes. The primary endpoint was the median number of HIV-DNA copies per 106 peripheral blood mononuclear cells (PBMC) at month 24, analysed in the modified intention-to-treat population, defined as all patients who started their assigned treatment. This study is registered with ClinicalTrials.gov, number NCT01033760. Findings Between April 26, 2010, and July 13, 2011, 110 patients were enrolled, of whom 92 were randomly assigned and 90 started treatment (45 in each treatment group). Six (13%) patients in the intensive cART group and two (4%) in the standard cART group discontinued before month 24. At month 24, HIV-DNA loads were similar between groups (2·35 [IQR 2·05–2·50] log10 per 106 PBMC in the intensive cART group vs 2·25 [1·71–2·55] in the standard cART group; p=0·21). Eight grade 3–4 clinical adverse events were reported in seven patients in the intensive cART group and seven grade 3–4 clinical adverse events were reported in seven patients in the standard cART group. Three serious clinical adverse events occurred: two (pancreatitis and lipodystrophy) in the standard cART group, which were regarded as treatment related, and one event (suicide attempt) in the intensive cART group that was unrelated to treatment. Interpretation After 24 months, cART intensified with raltegravir and maraviroc did not have a greater effect on HIV blood reservoirs than did standard cART. These results should help to design future trials of treatments aiming to decrease the HIV reservoir in patients with primary HIV-1 infection. Funding Inserm–ANRS, Gilead Sciences, Janssen Pharmaceuticals, Merck, and ViiV Laboratories.